2012
DOI: 10.1007/s12529-012-9246-1
|View full text |Cite
|
Sign up to set email alerts
|

Modern Health Worries, Subjective Health Complaints, Health Care Utilization, and Sick Leave in the Norwegian Working Population

Abstract: Subjective health complaints and concerns about aspects of modern life affecting health are very common, even among healthy workers. Women have more complaints and more concerns compared to men. Within the health care system, it may be advantageous to pay close attention to the association between high levels of MHW and high levels of SHC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 22 publications
3
23
3
Order By: Relevance
“…No significant association was found with prevalence of medication, registered or unprescribed. Results are generally in line with the existing body of evidence in this field [2,17,[13][14][15][16][17][18][19][20]. Furthermore, a strong association was found between MHW and general perceived environmental sensitivity, with the latter being a statistical mediator of the relation between worries and the examined outcomes in the present analyses.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…No significant association was found with prevalence of medication, registered or unprescribed. Results are generally in line with the existing body of evidence in this field [2,17,[13][14][15][16][17][18][19][20]. Furthermore, a strong association was found between MHW and general perceived environmental sensitivity, with the latter being a statistical mediator of the relation between worries and the examined outcomes in the present analyses.…”
Section: Discussionsupporting
confidence: 91%
“…A growing body of studies has shown an association between MHW and several health and behavioral outcomes such as self-reported NSPS, healthcare utilization, use of alternative medicine, health anxiety, somatosensory amplification, depression and lower health-related quality of life [2,13,[14][15][16][17][18][19][20]. The exact role though of worries in the context of environmental health has not been settled.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of LBP are categorized as nonspecific, as opposed to nerve root or serious spinal pathology (Henschke et al 2009). Nonspecific conditions with no clear somatic pathology and a high degree of comorbidity are prevalent in the general population, as illustrated in several European studies (Indregard et al 2012;Roelen et al 2010). We refer to these conditions as Subjective Health Complaints (SHC).…”
Section: Introductionmentioning
confidence: 96%
“…Subjective health complaints (SHC), such as musculoskeletal and mental health complaints, have a high prevalence in the general population [1, 2]. SHC refers to complaints without a pathophysiological explanation or where the pathological findings are disproportionate to the illness experience [3].…”
Section: Introductionmentioning
confidence: 99%